MUTU PELAYANAN KESEHATAN BPJS MANDIRI DI WILAYAH PUSKESMAS TANJUNG SELAMAT KECAMATAN PADANG TUALANG KABUPATEN LANGKAT (Ditinjau dari Persepsi Pasien) - Erlina Erlina; Irawati A Kahar; Frida Lina Tarigan (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
The quality of health services at the Public Health Center (PHC) is the main indicator of the performance of the PHC. The purpose of this study was to determine the quality of health services held by PHC of Tanjung Selamat in Padang Tualang Sub-District, Langkat District based on patient perceptions of Mandiri BPJS members and establish improvement strategies. The focus of research is reliability, responsiveness, assurance, empathy, and tangibles. This study includes the type of qualitative research, research data are primary data and secondary data collected through interviews, observation, and documentation study. To check the validity of the data, triangulation techniques are used. The collected data is then analyzed through data reduction, data display, and conclusion withdrawals. The results showed that reliability, responsiveness, assurance, and empathy in PHC of Tanjung Selamat in Padang Tualang Sub-District, Langkat District were good or quality but the tangibles were still not good or lacking in quality. In addition, this study found several problems including a lack of adequate facilities/infrastructure and a lack of motivation to improve capacity for employees of the PHC of Tanjung Selamat in Padang Tualang Sub-District, Langkat District. Based on the results of this study, the improvement strategy needed at the PHC of Tanjung Selamat in Padang Tualang Sub-District, Langkat District is to add facilities/infrastructure to health services and improve the quality of providers